Rancangan Instrument Approach Procedure Konvensional pada Rencana Perpanjangan Runway 09 di Bandara I Gusti Ngurah Rai Bali - beryl akmal, muhammad; Sadiatmi, Rini; Trio Putra, Gilang (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Based on its geographical location, Bali's I Gusti Ngurah Rai International Airport is one of the airports that gets the government's attention to be rearranged into a Super - Hub airport. In doing the rearrangement, the management carried out the development of Landside and Airside. This airside development is carried out by extending the runway as far as 400 m to the west using the sea reclamation method. The extension of runway 09 causes a shift in the runway threshold 09, so it is necessary to adjust the Instrument Approach Procedure (IAP) in accordance with the regulations of the Director General of Civil Aviation KP 209 in 2019. This study uses the Research and Development level 1 method by combining data processing and presentation (triangulation) to achive accurate data. This aim is to make recommendations for the design of the instrument approach procedure runway 09 according to user needs. This study concludes that the shift in the runway 09 threshold has an impact on several existing procedures. Users expect minimal changes in procedure adjustments to make it easier for users.